Water condensation in low pressure steam turbine : a nucleation theory - Part II - Mohsin, R.; Abd. Majid, Z. (Faculty of Chemical and Natural Resource Engineering, UTM, 2008)
In the study of the condensation phenomenon in the operation of steam turbine, the existence of two-phase flow in the low pressure stage becomes significant in causing problems regarding the blade life span and efficiency reduction. The increase of wetness percentage in the steam turbine could reduce the overall efficiency of steam turbine. This second part of study highlights the extent of the evolution of the nucleation theory and its significant impact to the steam turbine blading design. Despite the central position of being power driven mechanism, only limited number of study have been carried out regarding the problems associated with the operation and design of these machines in comparison with that given to other prime movers. This paper will introduce some basic concept of the early to recent study towards investigating the nucleation theory in low pressure steam turbine.